The chemical ordering and elasticity in FeCoNiAl1−xTix high-entropy alloys. (15th July 2019) - Huang, Shuo
Abstract: First-principle alloy theory is employed to explore the ordering-induced elastic anomaly in the FeCoNiAl1− x Ti x (0 ≤  x  ≤ 1) high-entropy alloys. The disordered and partially ordered solid solution structures are quantitatively described within unified models. A comparison is made between the elastic parameters of the hypothetical structures, and the presence of L12 phase is found to be responsible for the strong stability in shear deformation in the Ti-rich compositions. The results are in line with experimental observation, and suggest that a proper control of the ordering level can be applied for further optimization of the mechanical characteristics in high-entropy alloys. Graphical abstract: Unlabelled Image